Y2O3 (at) SiO2 (at) PPy (at) MnO2 wave-absorbing composite material with multilayer core-shell heterogeneous frost-like structure and preparation method of Y2O3 (at) SiO2 (at) PPy (at) MnO2 wave-absorbing composite material
By designing the Y2O3@SiO2@PPy@MnO2 wave absorbing composite material with multi-layer core-shell heterogeneous frost structure, the problem of high density and poor absorption performance of microwave absorbing materials in the existing technology is solved, and efficient and wide-band wave absorbing is achieved Performance and simplify the preparation process and reduce costs.
Patent Information
- Application Number
- CN202411468942.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-21
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-10-21
AI Technical Summary
Existing microwave absorbing materials have problems such as high density, poor absorption performance, single loss mechanism and poor matching performance, making it difficult to achieve low-cost, lightweight, ultra-thin, high-performance and wide-frequency absorption absorbing materials.
Design a multi-layer core-shell heterogeneous frost structure Y2O3@SiO2@PPy@MnO2 wave absorbing composite material, prepared by Stober method and ultrasonic reaction, forming a multi-layer core-shell microsphere and nanorod structure to optimize components Proportion and reaction conditions to improve absorbing performance.
Absorbing materials with small density, high absorption performance and wide absorption bandwidth are realized, which simplifies the preparation method and reduces production costs and significantly improves the absorption efficiency.
Smart Images

Figure CN119144284A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of microwave absorbing materials, and specifically designs a Y2O3@SiO2@PPy@MnO2 microwave absorbing composite material with a multi-layer core-shell heterogeneous frost-like structure and a preparation method thereof. Background Art
[0002] At present, the research on microwave absorbing materials has made significant progress and the technical level has been continuously improved. These materials achieve microwave absorption through mechanisms such as magnetic loss and dielectric loss. Specifically, in view of the problems of high density, narrow absorption band and limited application range of traditional absorbing materials, the research and development of low-cost, lightweight, ultra-thin, high-performance and broadband absorbing absorbing materials has become a hot topic in current research.
[0003] Commonly used microwave absorbing materials include dielectric loss materials such as carbon materials, MnO2, PPy, and magnetic loss materials such as magnetic metals. However, magnetic materials have the problems of high density and narrow effective bandwidth, which limits their application range.
[0004] Y2O3 is an important rare earth oxide. Its unique 4f electronic structure gives it tunable physical properties. It can be used to manufacture microwave magnetic materials and important materials for military use. However, a single material cannot meet the demand for high-performance absorption materials.
[0005] SiO2 is a wave-transmitting material that increases the reflection path of electromagnetic waves inside the material. The wave-absorbing performance of SiO2 itself may be relatively limited, and it usually needs to be compounded or modified with other wave-absorbing materials to obtain better wave-absorbing effects. For example, patent number CN202110516544.3 discloses a method for preparing an α-Fe2O3-doped silica nanoparticle wave-absorbing material, but the composite material prepared by this method has not yet met the -10dB standard.
[0006] PPy has a certain conductivity and can generate conductive loss through interaction with electromagnetic fields, converting electromagnetic wave energy into other forms of energy such as heat. In order to improve the wave absorption performance of polypyrrole-based composite materials, one of the research directions is to compound polypyrrole with other dielectric loss materials or magnetic materials. For example, patent number CN 113845880A discloses a silver nanowire @ polypyrrole-ferroferric oxide composite wave absorbing material and its preparation method, but the silver nitrate used is expensive, and the composite material has a narrow effective absorption bandwidth and thick thickness, which is very unfavorable for subsequent use.
[0007] In view of this, it is of great significance to overcome the shortcomings of high density, poor absorption performance, single loss mechanism and poor matching performance, and to prepare a new absorbing material with low density, high absorption performance and effective absorption bandwidth. Summary of the invention
[0008] In view of the shortcomings of the prior art, the present invention provides a Y2O3@SiO2@PPy@MnO2 microwave absorbing composite material with a multi-layer core-shell heterogeneous frost-like structure and a preparation method thereof. The microwave absorbing composite material prepared by the present invention has good microwave absorbing performance, and the preparation method is simple and the production cost is low, which solves the problems of poor absorption performance and single microwave absorption frequency band of microwave absorbing materials in the prior art.
[0009] The technical solution of the present invention is as follows:
[0010] A Y2O3@SiO2@PPy@MnO2 absorbing composite material with a multi-layer core-shell heterogeneous frost-like structure. The absorbing composite material is composed of multi-layer core-shell microspheres and nanorods, and presents a frost-like structure; the multi-layer core-shell microspheres use Y2O3 as the core material, and are sequentially coated with SiO2 layers and PPy layers; the nanorods are MnO2.
[0011] Furthermore, the particle size of the Y2O3 is 50-200nm.
[0012] Furthermore, the mass ratio of Y2O3 to SiO2 is 1:1.
[0013] Furthermore, the mass ratio of Y2O3 to PPy is 7.14:1.
[0014] Furthermore, the mass ratio of Y2O3 to MnO2 is 1:3.93-4.07.
[0015] A method for preparing the wave-absorbing composite material, the method comprising the following steps:
[0016] (1) Preparation of single-layer core-shell microspheres Y2O3@SiO2: Y2O3 was dispersed in a solvent at room temperature, and TEOS was added to prepare single-layer core-shell microspheres Y2O3@SiO2 coated with SiO2 by Stober reaction;
[0017] (2) Preparation of multilayer core-shell microspheres Y2O3@SiO2@PPy: The single-layer core-shell microspheres Y2O3@SiO2 obtained in step (1) are dispersed in deionized water, FeCl3·6H2O is added, and after mixing, pyrrole monomer is added to react at room temperature, and after treatment, multilayer core-shell microspheres Y2O3@SiO2@PPy are obtained;
[0018] (3) Preparation of Y2O3@SiO2@PPy@MnO2 microwave absorbing composite material: The multilayer core-shell microspheres Y2O3@SiO2@PPy obtained in step (2) are dispersed in deionized water, and then KMnO4 is added. Hydrochloric acid is added dropwise while stirring, and ultrasonication is performed. The mixture is transferred into a reactor for reaction. Finally, the Y2O3@SiO2@PPy@MnO2 microwave absorbing composite material is obtained by cooling, filtering, collecting the filter residue, washing, and drying.
[0019] Furthermore, in step (1), the solvent is an aqueous solution of ethanol with a volume fraction of 75%; the concentration of Y2O3 in the solvent is 0.11 mol / L, and the concentration of TEOS in the solvent is 0.42 mol / L; and the reaction time is 4 h.
[0020] Furthermore, in step (2), the concentration of Y2O3@SiO2 in deionized water is 0.07 mol / L; the concentration of FeCl3·6H2O in deionized water is 0.07-0.08 mol / L; the concentration of pyrrole monomer in deionized water is 0.165 mol / L; the reaction temperature is -2 to 0°C, and the reaction time is 4 hours.
[0021] Furthermore, in step (3), the concentration of Y2O3@SiO2@PPy in deionized water is 0.01 mol / L; the concentration of KMnO4 in deionized water is 0.083 mol / L; the mass percentage concentration of hydrochloric acid is 36-38%, and the volume ratio of hydrochloric acid to deionized water is 1:80 mL; the reaction temperature is 180°C, and the reaction time is 5-7 h.
[0022] The beneficial technical effects of the present invention are:
[0023] The present invention designs a multi-layer core-shell frost structure wave-absorbing composite material. The wave-absorbing composite material prepared by the present invention uses multi-layer core-shell microspheres Y2O3@SiO2@PPy as "frost branches". Specifically, Y2O3 is used as the core material, SiO2 is used as the middle layer, and the conductive polymer PPy is used as the outermost layer of the core-shell. SiO2 is a wave-transmitting material that increases the reflection path of electromagnetic waves inside the material; PPy effectively promotes the eddy current effect and enhances eddy current losses. MnO2, as a "frost branch", significantly increases its specific surface area and increases the propagation path and scattering times of electromagnetic waves inside the material. Compared with the prior art, such as the NiCo2O4@PPy composite material disclosed in Patent No. CN 117560915 A and the composite material MnO2 / Ti3C2 MXene in Patent No. CN 117641872 A, the wave-absorbing performance of the Y2O3@SiO2@PPy of the present invention is better.
[0024] The wave-absorbing composite material of the present invention uses a three-layer core-shell structure Y2O3@SiO2@PPy as a "frost branch" to not only greatly enrich the number of interfaces and strengthen the interface polarization effect, but also effectively curb the reflection, scattering and transmission of electromagnetic waves by adjusting the amount of each raw material, thereby significantly improving the wave-absorbing efficiency of the material. The rod-shaped MnO2 on the periphery acts as a "frost branch", and the rods and rods, and the rods and the core-shell jointly construct a complex conductive network, which strengthens the conductive loss and effectively improves the overall electromagnetic wave absorption efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 FT-IR graphs of the absorbing composite materials prepared in Examples 1-5 of the present invention, Comparative Examples 1-4, and the absorbing material of Comparative Example 5.
[0026] In the figure: (a) is the FT-IR graph of the absorbing composite materials prepared in Example 1, Comparative Examples 1-2, and the absorbing material of Comparative Example 5; (b) is the FT-IR graph of the absorbing composite materials prepared in Example 1-2, Comparative Examples 3-4, and the absorbing material of Comparative Example 5; (c) is the FT-IR graph of the absorbing composite materials prepared in Example 2 and Examples 3-5.
[0027] Figure 2 XRD diagrams of the microwave-absorbing composite materials prepared in Examples 1-5 and Comparative Examples 1-4 of the present invention and the microwave-absorbing material of Comparative Example 5.
[0028] In the figure: (a) is the XRD diagram of the absorbing composite material prepared in Example 1, Comparative Examples 1-2, and the absorbing material of Comparative Example 5; (b) is the XRD diagram of the absorbing composite material prepared in Example 2, Comparative Examples 3-4, and the absorbing material of Comparative Example 5; (c) is the XRD diagram of the absorbing composite material prepared in Examples 3-5 and the absorbing material of Comparative Example 5.
[0029] Figure 3 These are SEM images of the absorbing composite materials prepared in Examples 1-5 of the present invention, Comparative Examples 1-4, and the absorbing material of Comparative Example 5.
[0030] In the figure: (a) is a SEM picture of the absorbing material of comparative example 5 at 500nm; (b) is a SEM picture of the absorbing composite material of comparative example 1 at 500nm; (c) is a SEM picture of the absorbing composite material of embodiment 1 at 500nm; (d) is a SEM picture of the absorbing composite material of comparative example 2 at 500nm; (e) is a SEM picture of the absorbing composite material of comparative example 3 at 1μm; (f) is a SEM picture of the absorbing composite material of embodiment 2 at 1μm; (g) is a SEM picture of the absorbing composite material of comparative example 4 at 1μm; (h) is a SEM picture of the absorbing composite material of embodiment 3 at 2μm; (i) is a SEM picture of the absorbing composite material of embodiment 4 at 2μm; (j) is a SEM picture of the absorbing composite material of embodiment 5 at 2μm.
[0031] Figure 4 The electromagnetic parameters ε', ε", and tanδ of the absorbing composite materials prepared in Examples 1-5 and Comparative Examples 1-4 of the present invention and the absorbing material of Comparative Example 5 are ε Atlas.
[0032] In the figure: (a) is the electromagnetic parameter ε' spectrum; (b) is the electromagnetic parameter ε" spectrum; (c) is tanδ ε Atlas.
[0033] Figure 5 The attenuation coefficient curves of the wave-absorbing composite materials prepared in Examples 1-5 of the present invention, Comparative Examples 1-4, and the wave-absorbing material of Comparative Example 5 are shown.
[0034] Figure 6 3D reflection losses corresponding to different thicknesses of the absorbing composite materials prepared in Examples 1-5 of the present invention, Comparative Examples 1-4, and the absorbing material in Comparative Example 5.
[0035] In the figure: (a) is the 3D reflection loss corresponding to the absorbing material of comparative example 5 at different thicknesses; (b) is the 3D reflection loss corresponding to the absorbing composite material of comparative example 1 at different thicknesses; (c) is the 3D reflection loss corresponding to the absorbing composite material of embodiment 1 at different thicknesses; (d) is the 3D reflection loss corresponding to the absorbing composite material of comparative example 2 at different thicknesses; (e) is the 3D reflection loss corresponding to the absorbing composite material of comparative example 3 at different thicknesses; (f) is the 3D reflection loss corresponding to the absorbing composite material of embodiment 2 at different thicknesses; (g) is the 3D reflection loss corresponding to the absorbing composite material of comparative example 4 at different thicknesses; (h) is the 3D reflection loss corresponding to the absorbing composite material of embodiment 3 at different thicknesses; (i) is the 3D reflection loss corresponding to the absorbing composite material of embodiment 4 at different thicknesses; (j) is the 3D reflection loss corresponding to the absorbing composite material of embodiment 5 at different thicknesses.
[0036] Figure 7 2D reflection losses corresponding to different thicknesses of the absorbing composite materials prepared in Examples 1-5 of the present invention, Comparative Examples 1-4, and the absorbing material in Comparative Example 5.
[0037] In the figure: (a) is the 2D reflection loss corresponding to the absorbing material of comparative example 5 at different thicknesses; (b) is the 2D reflection loss corresponding to the absorbing composite material of comparative example 1 at different thicknesses; (c) is the 2D reflection loss corresponding to the absorbing composite material of embodiment 1 at different thicknesses; (d) is the 2D reflection loss corresponding to the absorbing composite material of comparative example 2 at different thicknesses; (e) is the 2D reflection loss corresponding to the absorbing composite material of comparative example 3 at different thicknesses; (f) is the 2D reflection loss corresponding to the absorbing composite material of embodiment 2 at different thicknesses; (g) is the 2D reflection loss corresponding to the absorbing composite material of comparative example 4 at different thicknesses; (h) is the 2D reflection loss corresponding to the absorbing composite material of embodiment 3 at different thicknesses; (i) is the 2D reflection loss corresponding to the absorbing composite material of embodiment 4 at different thicknesses; (j) is the 2D reflection loss corresponding to the absorbing composite material of embodiment 5 at different thicknesses.
[0038] Figure 8 It is a Cole-Cole plot of the microwave-absorbing composite materials prepared in Examples 1-5 of the present invention, Comparative Examples 1-4, and the microwave-absorbing material of Comparative Example 5.
[0039] In the figure: (a) is a Cole-Cole diagram of the absorbing material of comparative example 5; (b) is a Cole-Cole diagram of the absorbing composite material of comparative example 1; (c) is a Cole-Cole diagram of the absorbing composite material of embodiment 1; (d) is a Cole-Cole diagram of the absorbing composite material of comparative example 2; (e) is a Cole-Cole diagram of the absorbing composite material of comparative example 3; (f) is a Cole-Cole diagram of the absorbing composite material of embodiment 2; (g) is a Cole-Cole diagram of the absorbing composite material of comparative example 4; (h) is a Cole-Cole diagram of the absorbing composite material of embodiment 3; (i) is a Cole-Cole diagram of the absorbing composite material of embodiment 4; (j) is a Cole-Cole diagram of the absorbing composite material of embodiment 5. DETAILED DESCRIPTION
[0040] The present invention is described in detail below in conjunction with the accompanying drawings and embodiments.
[0041] The yttrium oxide particles used in the following examples / comparative examples of the present invention have a particle size of 100 nm and are purchased from Zhejiang Manli Nanotechnology Co., Ltd.
[0042] Example 1
[0043] A single-layer core-shell microsphere Y2O3@SiO2 wave-absorbing composite material, the preparation method of which is as follows:
[0044] At room temperature, Y2O3 (4 g, 0.018 mol) was dispersed in 160 mL of 75% ethanol solution (V 乙醇 :V 水 =3:1), ultrasonic treatment for 30 min, and then 0.067 mol of TEOS (i.e., the concentration of TEOS is 0.42 mol / L) was added dropwise, and then 16 mL of 25% ammonia water was added dropwise at a speed of 240 rpm, and the single-layer core-shell microspheres Y2O3@SiO2 coated with Y2O3 were prepared by the Stober method for 4 h, washed with deionized water and ethanol, centrifuged at 10000 rpm for 5 min, and the supernatant was discarded. The above centrifugation operation was repeated for multiple times, and the residue was collected by filtration and dried at 80 ° C for 12 h to obtain the pure single-layer core-shell microspheres Y2O3@SiO2 (the mass ratio of Y2O3 to SiO2 was 1:1 after detection), named YS B , YS B It is evenly mixed with solid paraffin in a mass ratio of 3:7, and then pressed into a sample with an outer diameter of 7.00mm, an inner diameter of 3.04mm, and a thickness of about 2mm using a special pressing ring mold for subsequent performance testing.
[0045] Example 2
[0046] A Y2O3@SiO2@PPy wave-absorbing composite material with a multilayer core-shell structure, and a preparation method thereof is as follows:
[0047] (1) Preparation of single-layer core-shell microspheres Y2O3@SiO2: The single-layer core-shell microspheres Y2O3@SiO2 were prepared according to the preparation method of Example 1 to obtain pure single-layer core-shell microspheres Y2O3@SiO2, named YS B .
[0048] (2) Preparation of multilayer core-shell microspheres Y2O3@SiO2@PPy: 0.014 mol of the single-layer core-shell microspheres Y2O3@SiO2 obtained in step (1) were dispersed in 200 mL of deionized water, and 0.015 mol of FeCl3·6H2O was added. After mixing evenly, 0.033 mol of pyrrole monomer was slowly added at 240 rpm and 0°C for 4 h. The microspheres were washed with deionized water and ethanol, centrifuged at 8000 rpm for 10 min, and the supernatant was discarded. The above centrifugation operation was repeated several times, and the residue was collected by filtration and dried at 80°C for 8 h to obtain multilayer core-shell microspheres Y2O3@SiO2@PPy (the mass ratio of Y2O3 to PPy was 7.14:1), which were named YS B P B , YS B P BIt is evenly mixed with solid paraffin in a mass ratio of 3:7, and then pressed into a sample with an outer diameter of 7.00mm, an inner diameter of 3.04mm, and a thickness of about 2mm using a special pressing ring mold for subsequent performance testing.
[0049] Example 3
[0050] A Y2O3@SiO2@PPy@MnO2 wave-absorbing composite material with a multi-layer core-shell heterogeneous frost-like structure, and a preparation method thereof is as follows:
[0051] (1) Preparation of single-layer core-shell microspheres Y2O3@SiO2: The single-layer core-shell microspheres Y2O3@SiO2 were prepared according to the preparation method of Example 1 to obtain pure single-layer core-shell microspheres Y2O3@SiO2, named YS B .
[0052] (2) Preparation of multilayer core-shell microspheres Y2O3@SiO2@PPy: The multilayer core-shell microspheres Y2O3@SiO2@PPy were prepared according to the preparation method of step (2) of Example 2, and were named YS B P B .
[0053] (3) 0.0011 mol of the multilayer core-shell microsphere Y2O3@SiO2@PPy obtained in step (2) was dispersed in 120 mL of deionized water, and then 0.01 mol of KMnO4 was added, and 1.5 mL of 36% to 38% hydrochloric acid was added dropwise at 300 rpm, and ultrasonic treatment was performed for 15 min. The mixture was then transferred to a Teflon-lined stainless steel reactor and reacted at 180°C for 5 h. The mixture was cooled, filtered, the residue was collected, washed, and dried at 80°C for 12 h to obtain a Y2O3@SiO2@PPy@MnO2 absorbing composite material (the mass ratio of Y2O3 to MnO2 was 1:3.93, which was named YS B P B M A , YS B P B M A It is evenly mixed with solid paraffin in a mass ratio of 3:7, and then pressed into a sample with an outer diameter of 7.00mm, an inner diameter of 3.04mm, and a thickness of about 2mm using a special pressing ring mold for subsequent performance testing.
[0054] Example 4
[0055] A Y2O3@SiO2@PPy@MnO2 wave-absorbing composite material with a multi-layer core-shell heterogeneous frost-like structure, and a preparation method thereof is as follows:
[0056] (1) Preparation of single-layer core-shell microspheres Y2O3@SiO2: The single-layer core-shell microspheres Y2O3@SiO2 were prepared according to the preparation method of Example 1 to obtain pure single-layer core-shell microspheres Y2O3@SiO2, named YSB .
[0057] (2) Preparation of multilayer core-shell microspheres Y2O3@SiO2@PPy: The multilayer core-shell microspheres Y2O3@SiO2@PPy were prepared according to the preparation method of step (2) of Example 2, and were named YS B P B .
[0058] (3) 0.0011 mol of the multilayer core-shell microsphere Y2O3@SiO2@PPy obtained in step (2) was dispersed in 120 mL of deionized water, and then 0.01 mol of KMnO4 was added, and 1.5 mL of hydrochloric acid with a concentration of 36% to 38% was added dropwise at a speed of 300 rpm. The mixture was ultrasonically treated for 15 min, and then transferred to a Teflon-lined stainless steel reactor. After high-temperature reaction at 180°C for 6 h, the mixture was cooled, filtered, the filter residue was collected, washed, and dried at 80°C for 12 h to obtain a Y2O3@SiO2@PPy@MnO2 absorbing composite material (the mass ratio of Y2O3 to MnO2 was 1:4.02), which was named YS B P B M B , YS B P B M B It is evenly mixed with solid paraffin in a mass ratio of 3:7, and then pressed into a sample with an outer diameter of 7.00mm, an inner diameter of 3.04mm, and a thickness of about 2mm using a special pressing ring mold for subsequent performance testing.
[0059] Example 5
[0060] A Y2O3@SiO2@PPy@MnO2 wave-absorbing composite material with a multi-layer core-shell heterogeneous frost-like structure, and a preparation method thereof is as follows:
[0061] (1) Preparation of single-layer core-shell microspheres Y2O3@SiO2: The preparation was carried out according to the preparation method of Example 1 to obtain pure single-layer core-shell microspheres Y2O3@SiO2, named YS B .
[0062] (2) Preparation of multilayer core-shell microspheres Y2O3@SiO2@PPy: The multilayer core-shell microspheres Y2O3@SiO2@PPy were prepared according to the preparation method of step (2) of Example 2, and were named YS B P B .
[0063] (3) 0.0011 mol of the multilayer core-shell microsphere Y2O3@SiO2@PPy obtained in step (2) was dispersed in 120 mL of deionized water, and then 0.01 mol of KMnO4 was added, and 1.5 mL of 36% to 38% hydrochloric acid was added dropwise at 300 rpm, and ultrasonic treatment was performed for 15 min. The mixture was then transferred to a Teflon-lined stainless steel reactor and reacted at 180°C for 7 h. Finally, the mixture was cooled, filtered, the residue was collected, washed, and dried at 80°C for 12 h to obtain a Y2O3@SiO2@PPy@MnO2 absorbing composite material (the mass ratio of Y2O3 to MnO2 was 1:4.07), which was named YS B P B M C , YS B P B M C It is evenly mixed with solid paraffin in a mass ratio of 3:7, and then pressed into a sample with an outer diameter of 7.00mm, an inner diameter of 3.04mm, and a thickness of about 2mm using a special pressing ring mold for subsequent performance testing.
[0064] Comparative Example 1
[0065] A single-layer core-shell microsphere Y2O3@SiO2 wave-absorbing composite material, the preparation method of which is as follows:
[0066] At room temperature, Y2O3 (4 g, 0.018 mol) was dispersed in 160 mL of 75% ethanol solution (V 乙醇 :V 水 =3:1), ultrasonic treatment for 30 min, and then 0.034 mol of TEOS (i.e., the concentration of TEOS is 0.21 mol / L) was added dropwise, and then 8 mL of 25% ammonia water was added dropwise at a speed of 240 rpm, and the single-layer core-shell microspheres Y2O3@SiO2 coated with SiO2 were prepared by the Stober method for 4 h. The single-layer core-shell microspheres Y2O3@SiO2 with Y2O3 coated were washed with deionized water and ethanol, centrifuged at 10000 rpm for 5 min, the supernatant was discarded, the above centrifugal operation was repeated for multiple times, and the residue was collected by filtration and dried at 80 ° C for 12 h to obtain the pure single-layer core-shell microspheres Y2O3@SiO2 (the mass ratio of Y2O3 to SiO2 was 2:1 after detection), named YS A , YS A It is evenly mixed with solid paraffin in a mass ratio of 3:7, and then pressed into a sample with an outer diameter of 7.00mm, an inner diameter of 3.04mm, and a thickness of about 2mm using a special pressing ring mold for subsequent performance testing.
[0067] Comparative Example 2
[0068] A single-layer core-shell microsphere Y2O3@SiO2 wave-absorbing composite material, the preparation method of which is as follows:
[0069] At room temperature, Y2O3 (4 g, 0.018 mol) was dispersed in 160 mL of 75% ethanol solution (V 乙醇 :V 水 =3:1), ultrasonic treatment for 30 min, and then 0.10 mol of TEOS (i.e., the concentration of TEOS is 0.63 mol / L) was added dropwise, and then 24 mL of 25% ammonia water was added dropwise at a speed of 240 rpm, and the single-layer core-shell microspheres Y2O3@SiO2 coated with SiO2 were prepared by the Stober method for 4 h, washed with deionized water and ethanol, centrifuged at 10000 rpm for 5 min, and the supernatant was discarded. The above centrifugation operation was repeated for multiple times, and the residue was collected by filtration and dried at 80 ° C for 12 h to obtain the pure single-layer core-shell microspheres Y2O3@SiO2 (the mass ratio of Y2O3 to SiO2 was 1:2 after detection), named YS C , YS C It is evenly mixed with solid paraffin in a mass ratio of 3:7, and then pressed into a sample with an outer diameter of 7.00mm, an inner diameter of 3.04mm, and a thickness of about 2mm using a special pressing ring mold for subsequent performance testing.
[0070] Comparative Example 3
[0071] A Y2O3@SiO2@PPy wave-absorbing composite material with a multilayer core-shell structure, and a preparation method thereof is as follows:
[0072] (1) Preparation of single-layer core-shell microspheres Y2O3@SiO2: The preparation was carried out according to the preparation method of Example 1 to obtain pure single-layer core-shell microspheres Y2O3@SiO2, named YS B .
[0073] (2) Preparation of multilayer core-shell microspheres Y2O3@SiO2@PPy: 0.014 mol of the single-layer core-shell microspheres Y2O3@SiO2 obtained in step (1) were dispersed in 200 mL of deionized water, and 0.015 mol of FeCl3·6H2O was added. After mixing evenly, 0.017 mol of pyrrole monomer was slowly added at 240 rpm and 0°C for 4 h. The microspheres were washed with deionized water and ethanol, centrifuged at 8000 rpm for 10 min, and the supernatant was discarded. The above centrifugation operation was repeated several times, and the residue was collected by filtration and dried at 80°C for 8 h to obtain multilayer core-shell microspheres Y2O3@SiO2@PPy (the mass ratio of Y2O3 to PPy was 15.83:1), which were named YS B P A , YS B P AIt is evenly mixed with solid paraffin in a mass ratio of 3:7, and then pressed into a sample with an outer diameter of 7.00mm, an inner diameter of 3.04mm, and a thickness of about 2mm using a special pressing ring mold for subsequent performance testing.
[0074] Comparative Example 4
[0075] A Y2O3@SiO2@PPy wave-absorbing composite material with a multilayer core-shell structure, and a preparation method thereof is as follows:
[0076] (1) Preparation of single-layer core-shell microspheres Y2O3@SiO2: The preparation was carried out according to the preparation method of Example 1 to obtain pure single-layer core-shell microspheres Y2O3@SiO2, named YS B .
[0077] (2) Preparation of multilayer core-shell microspheres Y2O3@SiO2@PPy: 0.014 mol of the single-layer core-shell microspheres Y2O3@SiO2 obtained in step (1) were dispersed in 200 mL of deionized water, and 0.015 mol of FeCl3·6H2O was added. After mixing evenly, 0.051 mol of pyrrole monomer was slowly added at 240 rpm and 0°C for 4 h. The microspheres were washed with deionized water and ethanol, centrifuged at 8000 rpm for 10 min, and the supernatant was discarded. The above centrifugation operation was repeated several times, and the residue was collected by filtration and dried at 80°C for 8 h to obtain multilayer core-shell microspheres Y2O3@SiO2@PPy (the mass ratio of Y2O3 to PPy was 5.72:1), which were named YS B P B , YS B P B It is evenly mixed with solid paraffin in a mass ratio of 3:7, and then pressed into a sample with an outer diameter of 7.00mm, an inner diameter of 3.04mm, and a thickness of about 2mm using a special pressing ring mold for subsequent performance testing.
[0078] Comparative Example 5
[0079] The absorbing material of comparative example 5 is Y2O3 with a particle size of 50-200nm, that is, the absorbing material of this comparative example is Y2O3 purchased directly, and Y2O3 and solid paraffin are evenly mixed in a mass ratio of 3:7, and then pressed into a sample with an outer diameter of 7.00mm, an inner diameter of 3.04mm, and a thickness of about 2mm by a special pressing ring mold for subsequent performance testing.
[0080] Comparative Example 6
[0081] A microsphere heterogeneous frost-like structure Y2O3@MnO2 wave-absorbing composite material, the preparation method of which is as follows:
[0082] At room temperature, Y2O3 (4g, 0.018mol) was dispersed in 120mL deionized water and ultrasonicated for 10min. Then 0.01mol of KMnO4 was added, and 1.5mL of 36% to 38% hydrochloric acid was added dropwise at 300rpm, and ultrasonicated for 15min. Then, the mixture was transferred to a Teflon-lined stainless steel reactor, and reacted at 180℃ for 6h. Finally, the mixture was cooled, filtered, the residue was collected, washed, and dried at 80℃ for 12h to obtain a Y2O3@MnO2 absorbing composite material, named YM B , YM B It is evenly mixed with solid paraffin in a mass ratio of 3:7, and then pressed into a sample with an outer diameter of 7.00mm, an inner diameter of 3.04mm, and a thickness of about 2mm using a special pressing ring mold for subsequent performance testing.
[0083] Comparative Example 7
[0084] A Y2O3@SiO2@MnO2 wave-absorbing composite material with a core-shell heterogeneous frost-like structure, and a preparation method thereof is as follows:
[0085] (1) Preparation of core-shell microspheres Y2O3@SiO2: The preparation was carried out according to the preparation method of Example 1 to obtain pure single-layer core-shell microspheres Y2O3@SiO2, named YS B .
[0086] (2) 0.0016 mol of the core-shell microsphere Y2O3@SiO2 obtained in step (1) was dispersed in 120 mL of deionized water, and then 0.01 mol of KMnO4 was added, and 1.5 mL of 36% to 38% hydrochloric acid was added dropwise at 300 rpm, and ultrasonic treatment was performed for 15 min. The mixture was then transferred to a Teflon-lined stainless steel reactor, and reacted at 180°C for 6 h. Finally, the mixture was cooled, filtered, the residue was collected, washed, and dried at 80°C for 12 h to obtain a Y2O3@SiO2@MnO2 absorbing composite material, which was named YS B M B , YS B M B It is evenly mixed with solid paraffin in a mass ratio of 3:7, and then pressed into a sample with an outer diameter of 7.00mm, an inner diameter of 3.04mm, and a thickness of about 2mm using a special pressing ring mold for subsequent performance testing.
[0087] Comparative Example 8
[0088] A Y2O3@SiO2@PPy@MnO2 wave-absorbing composite material with a multi-layer core-shell heterogeneous frost-like structure, and a preparation method thereof is as follows:
[0089] (1) Preparation of single-layer core-shell microspheres Y2O3@SiO2: The single-layer core-shell microspheres Y2O3@SiO2 were prepared according to the preparation method of Example 1 to obtain pure single-layer core-shell microspheres Y2O3@SiO2, named YS B .
[0090] (2) Preparation of multilayer core-shell microspheres Y2O3@SiO2@PPy: The multilayer core-shell microspheres Y2O3@SiO2@PPy were prepared according to the preparation method of step (2) of Example 2, and were named YS B P B .
[0091] (3) 0.0011 mol of the multilayer core-shell microsphere Y2O3@SiO2@PPy obtained in step (2) was dispersed in 120 mL of deionized water, and then 0.02 mol of KMnO4 was added, and 3.0 mL of 36% to 38% hydrochloric acid was added dropwise at 300 rpm, and ultrasonic treatment was performed for 15 min. The mixture was transferred to a Teflon-lined stainless steel reactor and reacted at 180°C for 6 h. Finally, the mixture was cooled, filtered, the residue was collected, washed, and dried at 80°C for 12 h to obtain a Y2O3@SiO2@PPy@MnO2 absorbing composite material (the mass ratio of Y2O3 to MnO2 was 1:8.04), which was named YS B P B M B -2, YS B P B M B -2 and solid paraffin were mixed evenly in a mass ratio of 3:7, and then pressed into samples with an outer diameter of 7.00mm, an inner diameter of 3.04mm, and a thickness of about 2mm using a special pressing ring mold for subsequent performance testing.
[0092] Test Case
[0093] (1) FT-IR characterization of absorbing composite materials
[0094] The absorbing composite materials prepared in Examples 1-5 of the present invention, Comparative Examples 1-4 and the absorbing material of Comparative Example 5 were taken and the FT-IR spectra of each material were detected by Nicolet is10 Fourier transform infrared spectrometer. The results are as follows: Figure 1 shown.
[0095] from Figure 1 As shown in Figure (a), the peak of yttrium oxide is 553 cm -1 , and with the SiO2 coating, the peak becomes significantly weaker. At the same time, a peak at 1075cm -1 and 782cm -1 The new peaks, corresponding to the asymmetric stretching vibration and symmetric stretching vibration of Si-O bonds, prove the synthesis and existence of SiO2.
[0096] from Figure 1 As can be seen from the results in Figure (b), the characteristic peak of polypyrrole is clearly shown in the figure: 1557cm -1 The peak corresponding to the vibration of the pyrrole ring is 1209 cm -1 The stretching vibration mode of the CN bond is at 1065cm -1 and 934cm -1 The characteristic peak of 795cm is closely related to the out-of-plane vibration of =CH. -1 The peaks are attributed to the out-of-plane deformation vibration of CH; even if the doping conditions of PPy are changed, the above characteristic peaks do not shift significantly or disappear, indicating that polypyrrole in YS B Uniform coverage of the surface.
[0097] from Figure 1 As can be seen from the results in Figure (c), YS B P B M A , YS B P B M B , YS B P B M C The peak values of YS B P B There is no manganese dioxide peak. This may be because other peaks are stronger, which weakens the manganese dioxide peak.
[0098] (2) XRD characterization of microwave absorbing composite materials
[0099] The absorbing composite materials prepared in Examples 1-5 of the present invention, Comparative Examples 1-4 and the absorbing material of Comparative Example 5 were taken and the XRD patterns of the materials were detected by D2 PHASER A26-X1-A2E0B2A0 X-ray diffractometer. The results are as follows: Figure 2 shown.
[0100] from Figure 2 From the results in Figure (a), it can be seen that the obvious diffraction peaks correspond to the crystal planes of Y2O3 (JCPDS NO.41-1105), indicating the high purity and good crystallinity of Y2O3, but no obvious diffraction peaks attributable to SiO2 were observed in the XRD spectrum.
[0101] from Figure 2 As can be seen from the results in Figure (b), the multilayer core-shell structure YS B P A , YS B P B , YS B P CThey all show strong diffraction peaks at 20.75°, 29.15°, 33.69°, 48.47° and 57.59°, which correspond to the characteristic diffraction peaks of Y2O3, and the characteristic diffraction peaks of polypyrrole are almost invisible in the figure.
[0102] from Figure 2 As shown in the results of Figure (c), the multilayer core-shell heterogeneous frost-like structure YS B P B M A , YS B P B M B , YS B P B M C There are strong diffraction peaks at 12.7°, 18.1°, 28.8°, 37.5°, 49.8°, 52.8°, 60.2°, 69.7°, and 71.1°, which correspond to the characteristic diffraction peaks of MnO2, indicating the successful synthesis of MnO2.
[0103] (3) SEM characterization of microwave-absorbing composite materials
[0104] The absorbing composite materials prepared in Examples 1-5 of the present invention, Comparative Examples 1-4 and the absorbing material of Comparative Example 5 were taken, and the SEM images of each material were detected by a Hitachi SU8100 (Regulus8100) cold field emission scanning electron microscope. The results are as follows: Figure 3 shown.
[0105] from Figure 3 As can be seen in Figures (a), (b), (c), and (d), the surface structure of yttrium oxide changes significantly after being coated with a layer of SiO2. The surface of the material becomes relatively smooth, and the particle diameter increases significantly to about 200-300nm, which directly reflects the successful coating of the SiO2 layer. As the SiO2 content increases, the particle morphology becomes nearly round, but excessive addition leads to a certain degree of aggregation.
[0106] from Figure 3 As can be seen from Figures (e), (f), and (g), YS B The surface is evenly covered with a layer of polypyrrole shell, and the surface of the shell shows some protrusions. These protrusions are the floccules formed by polypyrrole during the self-polymerization process, which directly proves the successful synthesis of polypyrrole.
[0107] from Figure 3 As can be seen from Figures (h), (i), and (j), with the increase of reaction time, the morphology of rod-shaped manganese dioxide changes significantly, which is specifically manifested in the increase of diameter. B P BAs the key frost branch point, it not only effectively connects the rod-shaped manganese dioxide, but also promotes the formation of frost-like structures; the rod-shaped manganese dioxide extends like branches and is closely connected to the frost branch, together constructing this unique structure.
[0108] (4) Electromagnetic parameters of absorbing composite materials ε', ε", tanδ ε Characterization
[0109] The absorbing composite materials prepared in Examples 1-5 of the present invention, Comparative Examples 1-4 and the absorbing material of Comparative Example 5 were taken, and the electromagnetic parameters ε' (real part of dielectric constant), ε" (imaginary part of dielectric constant), tanδ ε (dielectric loss tangent), the result is as follows Figure 4 As shown. (Since the composite material is mainly composed of non-magnetic components Y2O3 and SiO2, the magnetic loss will not be further described)
[0110] from Figure 4 The results show that after the introduction of MnO2, the real part of the dielectric constant increases significantly, which indirectly increases the absorption performance; in addition, the imaginary part and the tangent value of the dielectric constant increase slightly.
[0111] (5) Attenuation coefficient curve corresponding to the absorbing composite material.
[0112] Take the absorbing composite materials prepared in Examples 1-5 of the present invention, Comparative Examples 1-4 and the absorbing material of Comparative Example 5, detect the electromagnetic parameters of each material by a DR-S vector network analyzer, calculate the attenuation coefficient corresponding to each material by an RL-Calculator, and draw a graph, as shown in FIG. Figure 5 As shown. Figure 5 The results show that after the introduction of MnO2, the attenuation coefficient has increased significantly, thereby increasing the microwave absorption performance.
[0113] (6) Characterization of 3D reflection loss and 2D reflection loss of absorbing composite materials at different thicknesses
[0114] The absorbing composite materials prepared in Examples 1-5 of the present invention, Comparative Examples 1-4, and the absorbing material of Comparative Example 5 were taken, and the electromagnetic parameters of each material were measured by a DR-S vector network analyzer, and the RL was calculated by RL-Calculator. The 3D reflection loss (3D-RL) and 2D reflection loss (2D-RL) corresponding to each material at different thicknesses were plotted using Origin. The results are as follows: Figure 6 and Figure 7 shown.
[0115] from Figure 6 Figures (a), (b), (c), (d) and Figure 7As can be seen in Figures (a), (b), (c), and (d), only YS B The reflection loss standard is met, and YS A With YS C All of them failed to cross the critical threshold of -10dB, showing relatively low electromagnetic wave absorption capacity; however, YS B The effective absorption bandwidth is limited, which limits its application scope to a certain extent.
[0116] from Figure 6 Figures (e), (f), (g) and Figure 7 As can be seen from (e), (f), and (g), with the change of the amount of pyrrole monomer added, YS B P A , YS B P B , YS B P C Showing different peak values of wave absorption performance, YS B P A At 16.14GHz and 5mm thickness, it achieved an excellent absorption performance of -37.8dB; subsequently, YS B P B By increasing the pyrrole content, a higher absorption performance of -42.3 dB was achieved at 16.79 GHz and 3 mm thickness, reflecting the positive effect of the increase in pyrrole content on the performance; however, further increasing the pyrrole monomer to YS B P C However, the absorbing performance slightly decreased to -41.3dB, indicating that there is an optimal balance between pyrrole content and absorbing performance, showing a trend of first increasing and then decreasing.
[0117] from Figure 6 Figures (h), (i), (j) and Figure 7 As can be seen from Figures (h), (i), and (j), after the introduction of MnO2, as the thickness of the absorbing composite material increases, the minimum RL gradually moves to the low-frequency region, and the absorbing performance of all samples is better than -10dB, meeting the standards for commercial applications. From the two-dimensional RL, it can be seen that the effective absorption bandwidth of different samples is different, and it is obvious that YS B P B M C The narrowest, and YS B P B M B In keeping with YS B P B M A While having similar bandwidth, it also exhibits the highest absorption performance.
[0118] (7) Characterization of the internal structure of the microwave-absorbing composite material system
[0119] The absorbing composite materials prepared in Examples 1-5 of the present invention, Comparative Examples 1-4 and the absorbing material of Comparative Example 5 were taken, and the electromagnetic parameters of each material were measured by a DR-S vector network analyzer. The Cole-Cole curves of each material were plotted with ε' as the abscissa and ε" as the ordinate. The results are shown in FIG. Figure 8 As shown. Figure 8 The results show that the Cole-Cole curve reveals the coexistence of polarization loss and conduction loss in the form of an intuitive semicircle and a tail straight line. The multiple semicircles on the curve prove that multiple polarization loss processes are in parallel. There is an obvious fluctuation phenomenon in the curve, which deeply reveals the large amount of polarization generated inside the material. On the one hand, the interface effect of the heterogeneous structure between different components in the absorbing composite material inevitably induces interface polarization; on the other hand, the structural defects that may exist inside the material have also become an important source of polarization loss. The two act together on the electromagnetic response of the material.
[0120] (8) Wave absorption performance test
[0121] The absorbing composite materials prepared in Examples 1-5 of the present invention and Comparative Examples 1-8 and the absorbing material of Comparative Example 5 were taken and the absorbing performance was tested by the coaxial method (coaxial method: the absorbing performance of the material is reflected by measuring the power of the electromagnetic wave returned after the electromagnetic wave passes through the material). First, the electromagnetic parameters of the material were measured by a DR-S vector network analyzer, and then the RL-Calculator software was used to calculate the magnetic wave absorption performance of each material. The results are shown in Table 1.
[0122] Table 1 The test results of the wave absorbing performance in Examples 1 to 4 and Comparative Examples 1 to 8.
[0123] Example / Comparative Example Thickness(mm) EAB(GHz) RLmin(dB) Example 1 4.5 0.64 -51.95 Example 2 3 0.98 -42.36 Example 3 2.4 2.76 -38.14 Example 4 1.8 4.58 -52.05 Example 5 2 1.85 -38.99 Comparative Example 1 5 0 -1.74 Comparative Example 2 5 0 -1.69 Comparative Example 3 5 1.47 -37.93 Comparative Example 4 2.8 0.42 -41.23 Comparative Example 5 3.3 0 -7.06 Comparative Example 6 5.0 0 -3.99 Comparative Example 7 2.2 1.67 -30.13 Comparative Example 8 2.4 0.67 -46.88
[0124] As shown in Table 1, the multilayer core-shell heterogeneous frost-like structure YS prepared in Examples 3-5 of the present invention B P B M A , YS B P B M B , YS B P B M C Compared with comparative examples 5-8, the YSPM composite material has excellent absorbing performance, which is due to the synergistic effect of multi-component optimization and special structural design to improve the absorbing performance.
[0125] By comparing Example 1, Comparative Examples 1-2 and Comparative Examples 5-6, it can be seen that after the surface of Y2O3 is coated with SiO2, the absorbing performance is only as good as that of YS B Improved, YS A and YS CThe others decreased, indicating that the SiO2 content has an effect on the absorbing performance, but the effect is limited; and the effective absorption bandwidth (EAB) is very narrow, less than 1GHz. When the Y2O3 surface is only coated with MnO2, the absorbing performance is very low, only reaching -3.99dB.
[0126] By comparing Example 2, Comparative Examples 3-4 and Comparative Example 7, it can be seen that when there is no PPy in Comparative Example 7, the absorption performance is only -30.13 dB; after depositing a layer of PPy, YS B P B Although the wave absorption performance is better than YS B (-51.95dB) is low, but its effective absorption bandwidth is improved by 0.34GHz; however, the content of PPy also affects the absorption performance of the material, such as YS B P A Although the effective absorption bandwidth has been improved, the thickness is relatively thick; YS B P C The effective absorption bandwidth is compared with YS B Therefore, the present invention improves the effective absorption bandwidth of the absorbing material by optimizing the deposition amount of PPy.
[0127] By comparing Example 2, Examples 3-5 and Comparative Example 8, it can be seen that after the introduction of MnO2, the absorption performance is better than that of YS B P B Improved. B P B M A When the thickness is 2.4mm, the absorption performance reaches -38.1dB, and the effective absorption bandwidth is 2.87GHz; B P B M B Compared to YS B P B M A The reaction time in step (3) was extended by 1 h. B P B M B The absorption performance of YS has been improved, and the effective absorption bandwidth has been widened to 4.58GHz. B P B M B -2 compared to YS B P B M B When the mass of MnO2 doubled during the preparation process, the performance reached -46.88dB, which is higher than YS B P B M A and YS B P B M C , lower than YSB P B M B , but the effective absorption bandwidth is narrow. B P B M B It has the best wave absorbing performance, especially in the medium and high frequency range, and can be used in military radar.
[0128] The present invention adjusts the dosage of each component in the multilayer core-shell structure, changes the reaction conditions, and then regulates the morphology and structure of the absorbing composite material to improve the absorbing performance. The multilayer core-shell frost Y2O3@SiO2@PPy@MnO2 absorbing material provided by the present invention has a stable structure, excellent absorbing performance, and a simple preparation method with low cost.
[0129] The above is only a preferred embodiment of the present invention, and the present invention is not limited to the above embodiments. It is understood that other improvements and changes directly derived or associated by those skilled in the art without departing from the spirit and concept of the present invention should be considered to be included in the protection scope of the present invention.
Claims
1. A Y2O3@SiO2@PPy@MnO2 wave-absorbing composite material having a multi-layer core-shell heterogeneous frost-like structure, characterized in that: The wave-absorbing composite material is composed of multi-layer core-shell microspheres and nanorods, and presents a frost-like structure; the multi-layer core-shell microspheres use Y2O3 as the core material, and are sequentially coated with SiO2 layers and PPy layers; the nanorods are MnO2.
2. The wave absorbing composite material according to claim 1, characterized in that: The particle size of the Y2O3 is 50-200nm.
3. The wave absorbing composite material according to claim 1, characterized in that: The mass ratio of Y2O3 to SiO2 is 1:
1.
4. The wave absorbing composite material according to claim 1, characterized in that: The mass ratio of Y2O3 to PPy is 7.14:
1.
5. The wave absorbing composite material according to claim 1, characterized in that: The mass ratio of Y2O3 to MnO2 is 1:3.93-4.
07.
6. A method for preparing the wave-absorbing composite material according to claim 1, characterized in that: The preparation method comprises the following steps: (1) Preparation of single-layer core-shell microspheres Y2O3@SiO2: Y2O3 was dispersed in a solvent at room temperature, and TEOS was added to prepare single-layer core-shell microspheres Y2O3@SiO2 coated with SiO2 by Stober reaction; (2) Preparation of multilayer core-shell microspheres Y2O3@SiO2@PPy: The single-layer core-shell microspheres Y2O3@SiO2 obtained in step (1) are dispersed in deionized water, FeCl3·6H2O is added, and after mixing, pyrrole monomer is added to react at room temperature, and after treatment, multilayer core-shell microspheres Y2O3@SiO2@PPy are obtained; (3) Preparation of Y2O3@SiO2@PPy@MnO2 microwave absorbing composite material: The multilayer core-shell microspheres Y2O3@SiO2@PPy obtained in step (2) are dispersed in deionized water, and then KMnO4 is added. Hydrochloric acid is added dropwise while stirring, and ultrasonication is performed. The mixture is transferred into a reactor for reaction. Finally, the Y2O3@SiO2@PPy@MnO2 microwave absorbing composite material is obtained by cooling, filtering, collecting the filter residue, washing, and drying.
7. The preparation method according to claim 6, characterized in that: In step (1), the solvent is an aqueous solution of ethanol with a volume fraction of 75%; the concentration of Y2O3 in the solvent is 0.11 mol / L, and the concentration of TEOS in the solvent is 0.42 mol / L; and the reaction time is 4 hours.
8. The preparation method according to claim 6, characterized in that: In step (2), the concentration of Y2O3@SiO2 in deionized water is 0.07 mol / L; the concentration of FeCl3·6H2O in deionized water is 0.07-0.08 mol / L; the concentration of pyrrole monomer in deionized water is 0.165 mol / L; the reaction temperature is -2 to 0°C, and the reaction time is 4 hours.
9. The preparation method according to claim 6, characterized in that: In step (3), the concentration of Y2O3@SiO2@PPy in deionized water is 0.0092 mol / L; the concentration of KMnO4 in deionized water is 0.083 mol / L; the mass percentage concentration of hydrochloric acid is 36-38%, and the volume ratio of hydrochloric acid to deionized water is 1:80; the reaction temperature is 180°C and the reaction time is 5-7h.
Citation Information
Patent Citations
Hierarchical structure wave absorbing agent and preparation method thereof
CN107708396A
Flower-like Y-shaped hexagonal ferrite-manganese dioxide nano-powder and preparation method thereof
CN109437325A
Preparation method of flexible radio frequency band wave-absorbing material with negative dielectricity and negative magnetic conductivity
CN110872179A
Modified carbon fiber-mullite ceramic wave-absorbing material with multilayer structure and preparation method of modified carbon fiber-mullite ceramic wave-absorbing material
CN115196951A
Preparation method and application of Co (at) SiO2 (at) PPy with hollow core-shell structure
CN117548684A
